The role of community-based organizations in educational partnerships for equity: perspectives from Singapore - Teng, Siao See; Wewalaarachchi, Thilanga Dilum; Najib, A'isyah; Lee, Hing Giap Justin (Frontiers in Education, 2025)
Cross-sector educational partnerships are increasingly seen as critical levers for addressing educational inequities, with a growing shift from transactional support models to collaborative equity-driven ones. Community-based organizations are often involved in the support ecology for underprivileged youths to provide additional resources and services such as tutoring, school supplies, and access to technology. While such efforts appear to help reduce absenteeism and drop-outs, improve academic performance, and enhance general development and welfare, the role such organizations play is less examined in research. While international scholarship highlights equitable partnerships and independent community-based organization as part of a sustainable approach to support underprivileged students, less is known about how this unfolds in highly centralized, state-directed contexts. The paper addresses this gap by offering a Singaporean perspective where educational partnerships are shaped by a state-led developmental framework that privileges academic meritocracy and performance-based outcomes. Focusing on community-based organizations, the paper examines how those supporting underprivileged youths operate within the dominant “Learning as Social Service” model. This model provides remedial support to help students “catch up” and succeed within the existing system rather than address structural inequities. A critical discourse analysis on the annual reports of two key selected organizations of this model further explores their approaches, contributions as well as limitations of their partnerships to educational equity. The analysis reveals that while the organizations are well-placed to provide needed support for underprivileged youths, their work mainly falls within the frame of compensatory meritocracy that limits the equity pursuit by treating educational gaps as technical deficits rather than systemic issues. The paper argues for a reimagining of educational partnerships through the lens of collaborative governance and equity-centered practice—transformative approaches that center on community ownership, student agency and holistic development to address education disparities more effectively. By offering a Singaporean perspective on the intersection of educational equity and meritocratic culture, this paper contributes to the global discourse on how to strengthen equity in and through educational collaborations, particularly in outcomes-oriented, and highly structured environments.